Use of botulinum toxin for voiding dysfunction - Eldred-Evans, David; Dasgupta, Prokar (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
The use of botulinum toxin A (BoNT-A) has expanded across a range of lower urinary tract conditions. This review provides an overview of the current indications for BoNT-A in the lower urinary tract and critically evaluates the published evidence within each area. The classic application of BoNT-A has been in the management of refractory neurogenic detrusor overactivity (NDO) and overactive bladder (OAB). There is a large volume of high-quality evidence, including numerous randomized placebo-controlled trials, which demonstrate the efficacy of BoNT-A over a long follow-up period. The culmination of this robust evidence-base has led to onabotulinumtoxin A (onaBoNT-A) receiving regulatory approval as a second-line treatment for NDO at a dose of 200 U and OAB at dose of 100 U. Other applications for BoNT-A are used on an off-license basis and include interstitial cystitis/bladder pain syndrome (IC/BPS), benign prostatic hyperplasia (BPH), and detrusor sphincter dyssynergia (DSD). These applications are associated with a less mature evidence-base although the literature is rapidly evolving. At present, the results for painful bladder syndrome (PBS) are promising and BoNT-A injections are recommended as a fourth line option in recent international guidelines, although larger randomized study with longer follow-up are required to confirm the initial findings. As a treatment for DSD, BoNT-A injections have shown potential but only in a small number of trials of limited quality. No definite recommendation can be made based on the current evidence. Finally, the results for the treatment of BPH have been variable and recent high quality randomized controlled trials (RCTs) have suggested no benefit over placebo so at present it cannot be recommended for routine clinical practice. Future advances of BoNT-A include liposome encapsulated formulations which are being developed as an alternative to intravesical injections.